(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Wireless Sensor Networks (WSNs) is a distributed wireless network consists of large amount of sensor nodes which gather useful information from a variety of environment and these sensor nodes communicate with each other in a multi-hop radio networks, with the end goal of handing their processed data to the data collector or access point (AP) [1,2]. WSNs have many issues such as self-configuration, fault-tolerance, adaptation, flexibility, energy efficiency, security, scalability, interference, architectural issues, mobility and delay tolerance [3]. Among these issues the most critical issue is to save energy and interference. The aim of this study is to construct the network graph which is conflict free and has minimum interference and minimum energy consumption. We have MAC Access protocols but TDMA protocol is more efficient than other protocols because TDMA can eliminate collisions and remove the need for a back-off [4]. A TDMA scheduling algorithm is constructed for the wireless sensor network, which is based on the creation of separate independent sets of the representing network graph. Independent sets are employed to minimize the time slots needed for the complete transmission of data packets in the network. An algorithm has been developed to implement it and there are three different steps in the implementation of this algorithm. In first phase, the minimum independent sets of the network are constructed. In second phase, the conflict graph of given network graph has been created. In third phase, time slots are assigned to all the transmissions according to the independent sets which were created in first phase, so that all the data packets are transmitted to the access point (AP) or data collector. The simulation results indicate that the TDMA scheduling algorithm reduce the interference and energy consumption in the network graph.